Prevalence of specific immunoglobulin E and G against Aspergillus fumigatus in patients with asthma - Newsha Hedayati; Vida Mortezaee; Seyed Alireza Mahdaviani; Maryam Sadat Mirenayat; Maryam Hassanzad; Mihan Pourabdollah; Jalal Heshmatnia; Atefeh Fakharian; Guitti Pourdolat; Somayeh Sharifynia; Mahshid Vakili; Mahdi Abastabar; et al. (Mazandaran University of Medical Sciences, 2018)
Background and Purpose: Aspergillus fumigatus as a ubiquitous fungus can be found in the respiratory tract of the asthmatic and healthy people. The inhalation of Aspergillus spores leads to an immune response in individuals with asthma and results in the aggravation of the clinical symptoms. The present study aimed to investigate the prevalence of specific immunoglobulin E and G (IgE and IgG) against A.fumigatus in asthmatic patients. Materials and Methods: This study was conducted on 200 consecutive patients with moderate to severe asthma referring to Masih Daneshvari hospital Tehran, Iran, from January 2016 to February 2018. Skin prick test (SPT) was performed in all subjects with Aspergillus allergens. Moreover, all patients underwent specific IgE testing for Aspergillus using Hycor method. Enzyme immune assay was applied to measure total IgE and Aspergillus-specific IgG. Results: According to the results, the mean age of the patients was 45.8 years (age range: 18-78 years). The mean levels of total IgE and Aspergillus specific IgE in asthmatic patients were obtained as 316.3 (range: 6-1300 IU/ml) and 1.5 (range: 0.1- 61.3 IU/ml), respectively. Out of 200 patients, 27 (13.5%), 65 (32.5%), 22 (11.0%), and 86 (43.0%) cases had positive Aspergillus SPT, total IgE of > 417 IU/ml, Aspergillus-specific IgE, and IgG, respectively. The level of these variables in patients with severe asthma were 16 (16.5%), 36 (37.1%), 15 (15.5%), and 46 (47.4%), respectively. Conclusion: As the findings indicated, reactivity to Aspergillus is a remarkable phenomenon in asthmatic patients. It is also emphasised that the climatic condition may affect the positive rate of hypersensitivity to Aspergillus.